Kinematically redundant actuators, a solution for conflicting torque–speed requirements. (April 2019) - Verstraten, Tom; Furnémont, Raphael; López-García, Pablo; Rodriguez-Cianca, David; Vanderborght, Bram; Lefeber, Dirk
Robots often switch from highly dynamic motion to delivering high torques at low speeds. The actuation requirements for these two regimes are very different. As a consequence, the average efficiency of the actuators is typically much lower than the efficiency at the optimal working point. A potential solution is to use multiple motors for a single motor joint. This results in a redundant degree of freedom, which can be exploited to make the system more efficient overall. In this work, we explore the potential of kinematically redundant actuators in dynamic applications. The potential of a kinematically redundant actuator with two motors is evaluated against a single-motor equivalent in terms of operating range, maximum acceleration, and energy consumption. We discuss how the comparison is influenced by the design of the actuator and the way how the power is distributed over the input motors. Our results support the idea that kinematically redundant actuators can resolve the conflicting torque–speed requirements typical of robots.